2009
DOI: 10.1007/s11295-009-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers for kernel bitterness in almond

Abstract: Upon crushing, amygdalin present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…Sometimes, normally sweet cultivars that are heterozygous for this trait may be slightly bitter, possibly due to an alteration in the single dominant/recessive gene system (Dicenta et al, 2002). Some authors have also suggested that the genetic control of bitterness/sweetness in almond is more complex than originally proposed (Dicenta et al, 2007) and that the gene(s) determining bitterness remain to be identified (Sanchez-Perez et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes, normally sweet cultivars that are heterozygous for this trait may be slightly bitter, possibly due to an alteration in the single dominant/recessive gene system (Dicenta et al, 2002). Some authors have also suggested that the genetic control of bitterness/sweetness in almond is more complex than originally proposed (Dicenta et al, 2007) and that the gene(s) determining bitterness remain to be identified (Sanchez-Perez et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The kernel of bitter almond contains a colorless and crystalline glucoside known as amygdalin . In addition, it also contains an enzyme that may release hydrocyanic acid (HCN) and benzaldehyde upon chewing or crushing of the kernel . HCN is widely recognized as a lethal compound .…”
Section: Introductionmentioning
confidence: 99%
“…Bitter almond (Prunus dulcis var. Amara ) is one of the main varieties of almond and its oil is rich in monosaturated and polyunsaturated fatty acids, with oleic and linoleic acid as the major constituents, and contains naturally occurring vitamins such as A, B 1 , B 2 , B 6 , and E. 1,2 Almond oil provides useful nutrients to consumers. 3,4 The kernel of bitter almond contains a colorless and crystalline glucoside known as amygdalin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sk gene was mapped to linkage group 5 (G5), but none of the known candidate genes were found on G5. Therefore, Sánchez-Pérez et al (2010) saturated G5 with SSR primers, four of which were closely linked to the Sk locus and proved suitable for early, efficient selection against bitter kernel in a breeding programme after estimating the haplotypes of the parents and the identification of appropriate marker alleles.…”
mentioning
confidence: 99%